2001
DOI: 10.1016/s0006-3495(01)75809-2
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Direction of Kinesin-Driven Microtubule Movements along Microlithographic Tracks

Abstract: Motor proteins are able to move protein filaments in vitro. However, useful work cannot be extracted from the existing in vitro systems because filament motions are in random directions on two-dimensional surfaces. We succeeded in restricting kinesin-driven movements of microtubules along linear tracks by using micrometer-scaled grooves lithographically fabricated on glass surfaces. We also accomplished the extraction of unidirectional movement from the bidirectional movements along the linear tracks by adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
313
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(323 citation statements)
references
References 23 publications
6
313
4
Order By: Relevance
“…While there has been extensive work using patterned surfaces to redirect kinesin-driven microtubule transport (Hiratsuka et al, 2001;Hess et al, 2002;Moorjani et al, 2003), three dimensional confinement is a prerequisite for harnessing this biological system for microscale transport applications and for combining motor driven transport with pressuredriven microfluidics. Although kinesins immobilized on engineered surfaces can faithfully direct microtubules and their associated cargo, diffusion and convection in the bulk solution above the surface can easily cancel out any motordriven transport.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While there has been extensive work using patterned surfaces to redirect kinesin-driven microtubule transport (Hiratsuka et al, 2001;Hess et al, 2002;Moorjani et al, 2003), three dimensional confinement is a prerequisite for harnessing this biological system for microscale transport applications and for combining motor driven transport with pressuredriven microfluidics. Although kinesins immobilized on engineered surfaces can faithfully direct microtubules and their associated cargo, diffusion and convection in the bulk solution above the surface can easily cancel out any motordriven transport.…”
Section: Resultsmentioning
confidence: 99%
“…A number of groups have shown that three dimensional patterns on motor-coated surfaces will bend or buckle microtubules and reorient their direction (Hiratsuka et al, 2001;Hess et al, 2002;Clemmens et al, 2003;Moorjani et al, 2003;van den Heuvel et al, 2005). However, because the channels are open on their top, detachment from the surface prevents complete redirection and requires an influx of new microtubules to compensate for microtubules lost from the surface.…”
Section: Enclosed Microchannels Redirect Moving Microtubulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the potential applications of this system, it is thus necessary to develop a way to restrict the movement of filaments to one dimension along linear tracks for extended periods of time. Restricting kinesin-driven movement of microtubules along linear tracks was achieved by using micrometer-scaled grooves lithographically fabricated on glass surfaces [48][49][50]. In the presence of detergent, kinesin selectively adsorbed onto a glass surface from which the photoresist polymer has been removed, not on the photoresist polymer itself [50].…”
Section: Controlling the Direction Of Protein Filament Movement Usingmentioning
confidence: 99%